Peternakan Sapi Perah Rendah Emisi Metan : Usulan Pengembangan Badan Usaha Milik Pesantren - Muhammad Askari Zakariah; Hasbir Jaya Razak; Abdul Haris Nasution; Muhammad Zakariah; Yaldi Yaldi; Muhammad Alvarizal (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
The fulfillment of community nutrition, especially the increase in animal protein, can be increased by consuming milk, so there needs to be an increase in national milk production. Increasing national milk production can be done by initiating dairy farming in several areas. Products from dairy farms can be in the form of fresh milk, yogurt, ice cream, and cheese. Dairy farming with low methane emissions is a hope to reduce global warming, so there are several treatments that can be applied, namely the use of tannins, saponins, HMG CoA inhibitors, anthraquinones, nitrates and ration regulation, as well as the application of a biogas system as an alternative energy source.